Vocal risk mapping in classical singers: an analysis of the self-perception of voice quality, vocal fatigue, and singing voice handicap - Gomes, Diogenes; Moreti, Felipe [UNESP]; Behlau, Mara (Soc Brasileira Fonoaudiologia, 2024)
Purpose: To map the vocal risk in professional classical singers, analyzing their self-assessment of voice and self-perception of singing voice handicap and vocal fatigue. Methods: The study sample comprised of 52 professional classical choir singers, aged 31 to 72 years. They answered an online questionnaire in Google Forms, addressing their characterization, self-assessment of voice, the Voice Handicap Index-10 (VHI-10), Classical Singing Handicap Index (CSHI), and Vocal Fatigue Index (VFI). Results: The mean self-assessment of voice was between Good and Very good (1.2). The mean total VHI-10 score was 1.35, which is below the cutoff. The mean total CSHI score was 10.04. The mean total VFI score was 10.83, near the cutoff value. Classical singers who use their voice to give examples to students in their classes had higher scores in VHI-10 (p = 0.013), VFI voice restriction (p = 0.011), and VFI total score (p = 0.015). Besides, classical singers who already visited a Speech-Language Pathologist for voice problems had higher scores in VFI voice restriction (p = 0.040) and VFI recovery with voice rest (p = 0.019), in addition to correlations between instrument scores. Conclusion: Professional classical singers did not have voice handicaps. However, their self-perception of vocal fatigue was more present when the singing voice was used, such as giving examples with their own voice in class. Having had voice problems and visited a Speech-Language Pathologist in the past led to a greater perception of vocal recovery with rest.
Keywords: Voice; Singing; Self-Testing; Surveys and Questionnaires; Speech; Language and Hearing; Sciences